Assessment of drought tolerance of spring wheat - Zotova , L.P.; Zhumalin , A.Kh.; Savin , T.V.; Dzhataev , S.A.; Nuralov , A.S.; Khassanova, G.Zh. (Eurasian Journal of Applied Biotechnology, 2022)
Under the conditions of climate change, the problem of drought tolerance of agricultural crops is gaining an increasing effect. The lack of moisture remains a limiting factor and leads to a decrease in plant productivity in an arid climate. Therefore, an important direction of modern breeding, and today, is to increase the drought tolerance of plants when creating new varieties. To assess the resistance of plants, various methods are used, including laboratory ones. In physiological assessment, an effective method is to assess drought tolerance at the seedling stage. A deeper analysis is molecular labeling based on the genes that control the trait under study. The article presents the results of studies on the assessment of soft durum wheat samples for resistance to osmotic stress and their molecular screening using marker technology. The purpose of the research is to study and select the selected varieties of spring wheat on the basis of drought tolerance. The selected varieties and lines are recommended as a promising starting material in breeding for drought tolerance.